1995
DOI: 10.1016/1074-7613(95)90081-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine kinase syk is associated with and activated by the il-2 receptor: Possible link with the c-myc induction pathway

Abstract: The IL-2 receptor (IL-2R) consists of three subunits, the IL-2R alpha, IL-2R beta, and IL-2R gamma chains. The IL-2-induced proliferative signals emanate from the cytoplasmic domains of IL-2R beta and IL-2R gamma, but the nature and function of the signaling molecules that transmit these signals are not fully understood. Here, we report that Syk protein tyrosine kinase (PTK) is physically associated with IL-2R in peripheral blood lymphocytes. cDNA expression studies further revealed that this association is cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 52 publications
1
78
1
1
Order By: Relevance
“…The membrane proximal, the serine-rich region of IL-2Rfl is essential for activation of JAK-family PTKs [21] and Src-family Syk [22] as well as for c-myc gene induction. On the other hand, the membrane distal, the acidic region of IL-2R,fl is crucial for activation of Src-family PTKs and for c-fos and c-jun gene induction [23].…”
Section: Discussionmentioning
confidence: 99%
“…The membrane proximal, the serine-rich region of IL-2Rfl is essential for activation of JAK-family PTKs [21] and Src-family Syk [22] as well as for c-myc gene induction. On the other hand, the membrane distal, the acidic region of IL-2R,fl is crucial for activation of Src-family PTKs and for c-fos and c-jun gene induction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Activated PI 3-K is most likely then responsible for activation of its downstream kinase Akt (protein kinase B) and p70 S6 kinase (Ahmed et al, 1997;Kuo et al, 1992), which are involved in antiapoptotic and proliferative activities in response to IL-2 (Reif et al, 1997). In addition, the protein tyrosine (Hatakeyama et al, 1991;Minami et al, 1993Minami et al, , 1995Miyazaki et al, 1998;Figure 2). However, the biological signi®cance of their activation in vivo is not yet clear and requires further investigation.…”
Section: How Does Il-2 Transduce Its Signals?mentioning
confidence: 99%
“…The c-myc gene is induced in response to the proliferative signals elicited by extracellular stimuli, including IL-6. The non-receptor tyrosine kinases c-src (Barone and Courtneidge, 1995), syk (Minami et al, 1995), and Jak (Kawahara et al, 1995;Sakamaki et al, 1992;Watanabe et al, 1996), and the oncogenes, v-src, v-abl, bcr-abl, and v-akt all induce c-myc mRNA expression (Cleveland et al, 1989;Kuchino et al, 1985;Sovova et al, 1993;Stewart et al, 1995). Kiuchi et al (1999) showed that STAT3 mediates the induction of the c-myc gene upon gp130 stimulation.…”
Section: Il-6 and Stat3 In Plasmacytomagenesismentioning
confidence: 99%